2017
DOI: 10.1108/mrr-10-2015-0225
|View full text |Cite
|
Sign up to set email alerts
|

Operational or strategic benefits

Abstract: Purpose The purpose of this study is twofold: identifying important determinants for effective adoption of internet technologies in an organizational supply chain context and examining and classifying benefits yielded from internet adoption in supply chain. Design/methodology/approach A structured Web-based questionnaire was designed and administered to respondents to collect the primary data. With two reminders, this study managed to obtain 236 respondents from different industries in Malaysia. Structural e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 53 publications
(48 reference statements)
0
22
0
Order By: Relevance
“…The study developed a conceptual model consisting of four variables and five hypotheses, as shown in Figure 1. , where one showed strong disapproval and seven showed strongly agreed [40]. The third stage gathers respondents through digitalization training activities and clarifies research (exploratory) problems [40].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study developed a conceptual model consisting of four variables and five hypotheses, as shown in Figure 1. , where one showed strong disapproval and seven showed strongly agreed [40]. The third stage gathers respondents through digitalization training activities and clarifies research (exploratory) problems [40].…”
Section: Methodsmentioning
confidence: 99%
“…The first stage is to build a research model based on gaps in previous research and implement the model in tourism MSMEs through the formulation of hypotheses. The second stage developed a questionnaire on a scale of 1-7, where one showed strong disapproval and seven showed strongly agreed[40]. The third stage gathers respondents through digitalization training activities and clarifies research (exploratory) problems[40].…”
mentioning
confidence: 99%
“…Customer satisfaction is defined as "the overall attitudes regarding good or services after its acquisition and uses" (Mowen, 1995), in other words, it is viewed that satisfaction is the breadth to which the idea of product or service attainment to achieve the apprehension of buyers. If the attainment of the product is greater than the prediction of customers, the buyers are satisfied or very happy (Azam and Moha Asri, 2015; Haque et al, 2014;Tarofder et al, 2017). Furthermore, according to Zeithaml (1990), a customer's decision to consume or not the goods or services affected by various factors such as the fact that the quality of service.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It holds the potential to improve the overall business activities 29 . The recent research indicated that the Internet improved connectivity and interaction between firms and customers tightly and virtually 19,30,31 .…”
Section: Resource Based View and Supply Chain Technology Adoptionmentioning
confidence: 99%